Influência da idade da cana-de-açúcar na detecção sorológica de Xanthomonas albilineans e avaliação da resistência de variedades à escaldadura - Cuba Maidana, Lourdes Belén (2023)
Leaf scald disease (LSD) is one of the most important disease of sugarcane in Brazil. Two of the most employed control methods are the use of healthy seedcanes (seen in Chapter I) and resistant genotypes (seen in Chapter II). Laboratory diagnostic test is essential to obtain healthy seedcanes, and dot blot immunoassay is the serological technique employed for conventional planting. However, the adequate stalk age for sap extraction that provides reliable results in the dot blot method is unknown. Therefore, the objective of this work was to determine the stalk age that allows reliable diagnostic test of LSD. The variety employed was RB966928, infected with Xanthomonas albilineans (Xa) at a concentration of 10^6 cfu/mL. Sap extraction for LSD detection commenced at eight-month-old canes. The results showed that nine-month-old sugarcane plants exhibited escape, indicating that sap from plants of this age is not suitable for a reliable diagnosis of LSD. In Chapter II, assessment of genotype resistance to LSD was carried out by bacterial population of three cultivars (RB867515, RB92579, and RB966928) grown in pots. The results demonstrated that the Xa population density provided more information on the pathogen's colonization, making it the most appropriate, especially because it resembles the type of pathogen dissemination that occurs by harvester in Brazil, enlighten the cultivar reaction to it. Two of the most cultivated varieties in Brazil (RB92579 and RB966928) are highly susceptible to Xa.